2019
DOI: 10.1093/sysbio/syz027
|View full text |Cite
|
Sign up to set email alerts
|

Dense Geographic and Genomic Sampling Reveals Paraphyly and a Cryptic Lineage in a Classic Sibling Species Complex

Abstract: Incomplete or geographically biased sampling poses significant problems for research in phylogeography, population genetics, phylogenetics, and species delimitation. Despite the power of using genome-wide genetic markers in systematics and related fields, approaches such as the multispecies coalescent remain unable to easily account for unsampled lineages. The Empidonax difficilis/Empidonax occidentalis complex of small tyrannid flycatchers (Aves: Tyrannidae) is a classic example of widely distributed species … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 78 publications
(61 reference statements)
1
16
0
Order By: Relevance
“…For each individual crow, we calculated a maximum likelihood estimate of the genomic hybrid index and the average intertaxon heterozygosity across ancestry-informative loci using r package Introgress (Gompert & Buerkle, 2010 and hzar.makeCline1DNormal (Leaché et al, 2017;Linck et al, 2019;Scordato et al, 2017). For both mtDNA and overall nuDNA, we fit models without exponential tails, restricted parameter search space to a liberal yet reasonable range of values (cline centre > 500 km and < 3,500 km, cline width < 3,500 km; Derryberry et al, 2014) and fixed means, variances, and allele frequencies at cline ends to the observed values of the terminal populations (Linck et al, 2019;Lipshutz et al, 2019). We ran the Markov chain Monte Carlo (MCMC) optimizer for three iterative cycles using hzar.chain.doSeq, retaining the third run for subsequent analysis (Derryberry et al, 2014).…”
Section: Recent-generation Versus Lategeneration Hybridsmentioning
confidence: 99%
“…For each individual crow, we calculated a maximum likelihood estimate of the genomic hybrid index and the average intertaxon heterozygosity across ancestry-informative loci using r package Introgress (Gompert & Buerkle, 2010 and hzar.makeCline1DNormal (Leaché et al, 2017;Linck et al, 2019;Scordato et al, 2017). For both mtDNA and overall nuDNA, we fit models without exponential tails, restricted parameter search space to a liberal yet reasonable range of values (cline centre > 500 km and < 3,500 km, cline width < 3,500 km; Derryberry et al, 2014) and fixed means, variances, and allele frequencies at cline ends to the observed values of the terminal populations (Linck et al, 2019;Lipshutz et al, 2019). We ran the Markov chain Monte Carlo (MCMC) optimizer for three iterative cycles using hzar.chain.doSeq, retaining the third run for subsequent analysis (Derryberry et al, 2014).…”
Section: Recent-generation Versus Lategeneration Hybridsmentioning
confidence: 99%
“…However, decisions based solely on phylogenetic support need to be interpreted with caution, as phylogenetic topologies are sometimes unable to discriminate among alternative biogeographic hypotheses and are sensitive to incomplete sampling [18][19][20][21][22]. For example, monophyly can be recovered even in the case of multiple colonizations if sister lineages from the source areas went extinct or were not sampled due to insufficient geographical sampling.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that auditory modalities of communication may frequently be more important than visual ones in species recognition systems in the family. This is further supported by the lack of (Seutin & Simon, 1988; Winker, 1994), or extremely reduced (Manthey & Robbins, 2016) hybridization between vocally differentiated sibling species‐pairs in sympatry, and the extensive hybridization among lineages with morphological and vocal similarities (Linck et al, 2019; Rush et al., 2009). The structural differences in vocalizations between P. flaviventris and P. citreola exceed those of recently diverged sibling species‐pairs including Empidonax alnorum and E. trailli, and Contopus virens and C. sordidulus .…”
Section: Discussionmentioning
confidence: 95%